Impact of body weight at 19 weeks of Embrapa 051 layers on performance, nest utilization, and egg quality throughout the laying cycle - Tiago Araujo Rodrigues; Diciane Zeni Giehl; Juliana da Silva Camacho; Valdir Silveira de Ávila; Everton Luis Krabbe; Aline Arassiana Piccini Roll; Victor Fernando Buttow Roll (Ciência Rural)
ABSTRACT: A total of 860 Embrapa 051 pullets were allocated into three groups based on their 19-week body weights (heavy: 1.48 kg ± 0.01 SD, N= 172 birds, medium: 1.32 kg ± 0.039 SD, N= 516 birds, light: 1.19 kg ± 0.019 SD, N=172 birds) and housed in floor pens with nests for a 65-week production period. Heavy-weight birds exhibited higher egg production during weeks 24-28, while medium-weight hens surpassed heavy-weight counterparts between weeks 41-46, and light-weight hens outperformed heavy-weight birds in weeks 61-65. From weeks 57-65, no significant egg production differences were noted between heavy and medium-weight hens. Body weight at 19 weeks affected floor eggs, cracked eggs, and double-yolk eggs (P < 0.05) during weeks 22-34. Heavy-weight hens laid fewer floor eggs, medium-weight hens had fewer cracked eggs (0.3%), and light-weight hens produced fewer double-yolk eggs (1.1%). No significant impact of weight grouping on egg weight was observed. Results indicated that body weight at 19 weeks influences the laying cycle, with heavy, medium, and light-weight hens exhibiting distinct egg production patterns, nest use and egg quality traits at different phases of the cycle.